Analysis of the Application of Zaakwarneming for Doctors Who Perform Medical Actions Without Permission - Anita Kamilah; Kayla Andini Putri; Salsa Octaviani Suryanto; Ajeng Permana (Indonesian Journal of Law and Justice, 2025)
This research analyses the application of the concept of zaakwarneming in the medical world, specifically related to medical actions taken by doctors without the consent of patients or their families in emergency conditions. In Indonesian civil law, zaakwarneming allows a person to take care of the interests of others without power of attorney with the aim of protecting their interests. In the medical context, the application of this concept can justify the doctor's actions in situations where consent cannot be obtained in a timely manner. However, this action still poses legal and ethical dilemmas, especially in relation to the patient's right to autonomy as well as the doctor's professional responsibility. This research uses a mixed method, namely a quantitative approach through a community survey and a qualitative approach through a literature study. The survey results show that most people understand the importance of informed consent, but there are differences of opinion on whether doctors can act without consent in an emergency. Most respondents also support transparency and better communication between doctors and patients to avoid legal disputes. Legally, unauthorised medical action can have consequences in civil, criminal and administrative aspects. Therefore, clearer regulations are needed regarding the limits and responsibilities of doctors in the application of zaakwarneming. A more detailed Standard Operating Procedure (SOP) and public education on patient rights in medical services are expected to reduce the potential for legal disputes and increase legal certainty for medical personnel.